2022
DOI: 10.4251/wjgo.v14.i1.348
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of colorectal neoplasia in inflammatory bowel disease patients with post-inflammatory polyps: A systematic review and meta-analysis

Abstract: BACKGROUND Inflammatory bowel disease (IBD) patients with post-inflammatory polyps (PIPs) may carry an increased risk of colorectal neoplasia (CRN) including dysplasia and cancer. Current guidelines recommend active colonoscopy follow-up for these patients. However, the evidence for guidelines is still poor. In addition, some recent high-quality reports present a different view, which challenges the current guidelines. We hypothesize that IBD patients with PIPs are at increased risk of CRN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…IBD patients with PIPs were at an increased risk of CRC as compared to those without (Odds Ratio [OR] 2.01; 95% confidence interval [CI] 1.43-2.83). 5 However, large studies within the meta-analysis revealed a higher risk of colectomy and hospitalisation but not CRC. 3,4 Dysplasia and CRC are possible complications of IBD and increase both morbidity and mortality associated with IBD.…”
mentioning
confidence: 98%
“…IBD patients with PIPs were at an increased risk of CRC as compared to those without (Odds Ratio [OR] 2.01; 95% confidence interval [CI] 1.43-2.83). 5 However, large studies within the meta-analysis revealed a higher risk of colectomy and hospitalisation but not CRC. 3,4 Dysplasia and CRC are possible complications of IBD and increase both morbidity and mortality associated with IBD.…”
mentioning
confidence: 98%
“…Post-inflammatory polyps are defined endoscopically as cicatricial, digitiform protrusions of the mucosa that result from re-epithelization and excessive regeneration of ulcerated colonic mucosa [ 1 ]. They are often multiple and are more frequently found in the left colon [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-inflammatory polyps are a marker of previous episodes of severe inflammatory activity and several studies have shown an association with an increased risk of colorectal cancer, resulting in the need for shortened surveillance intervals [ 3 , 4 ]. However, a recent study reported an association between post-inflammatory polyps and increased risk of disease severity, more extensive colonic disease as well as higher rates of colectomy but not with an increased risk of colorectal cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation of the link between pseudopolyps and the risk of CRC lies in the fact that they represent an indirect marker of previous episodes of severe colonic inflammation and their incidence rises with the extent of colitis. It is also plausible that the presence of pseudopolyps, especially when they are very numerous, may make it more difficult for the operator to detect dysplastic lesions while performing surveillance colonoscopy [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%